Hubungan Tingkat Pengetahuan Remaja Terhadap Kejadian Pernikahan Dini di Wilayah Kelurahan Kereng Bangkirai RT 01/ RW 01 Kota Palangka Raya Tahun 2022: Corellation of Adolescent Knowledge Level to the Incidence of Early Marriage in the Village Area Kereng Bangkirai RT 01/RW 01 Palangka Raya City Year 2022 - Gracia Peni; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Adolescents are the initial seeds of a nation to become a better nation. However, teenagers drop out of school due to marriage at a young age. Based on data from the Central Statistics Agency (BPS) Central Kalimantan ranks second in cases of early marriage with a percentage of 20.2%. Factors causing early marriage that are often encountered are economic factors, education, parents, local customs and marriage due to accidents. The purpose of this study was to determine the relationship between the level of knowledge of adolescents on the incidence of early marriage. This study uses an analytical survey research design, the type of analytical survey research design using the Cross Sectional method, the sample in this study amounted to 59 teenagers in Kereng Bangkirai Village RT 01/RW 01 Palangka Raya City. Sampling by purposive sampling using inclusion criteria. Data analysis using Chi Square test. The results of the Chi Square test (P Value = 0.000 <0.05), which means there is a relationship. The conclusion in this study is that there is a relationship between the level of knowledge of adolescents on the incidence of early marriage. Therefore, to reduce early childhood, the quality of education should be improved.